Comparative Analysis of Us Policy to Manage Countries Either Through Direct Regime Change or International Sanctions - Muhammad Younus; Achmad Nurmandi; Rashid Minhas; Abdul Rehman; Imelda Zamjanah Rahmawati; Ibrahim Shah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The present research paper aims to provide a thorough comparative analysis of the United States strategies to exert control over other nations. Specifically, this study evaluates the effectiveness of the United States' two primary approaches: direct regime changes and the imposition of international sanctions. Through a rigorous analysis of historical case studies and policy outcomes, the primary objective of this study is to ascertain the approach that produces more favorable and enduring results. The present analysis explores the multifaceted dimensions of the economic, political, and humanitarian implications of both methods under investigation. By thoroughly examining these aspects, this study seeks to provide a comprehensive understanding of the strengths and weaknesses inherent in each approach.